Dissemination on the Use of Web-Based Educational Games to Enhance Student Learning Interest at UPTD SD Negeri 4 Bireuen, Kota Juang District, Bireuen Regency: Sosialisasi Pemanfaatan Game Edukasi Berbasis Web untuk Meningkatkan Minat Belajar Siswa di UPTD SD Negeri 4 Bireuen Kecamatan Kota Juang Kabupaten Bireuen - Afkar Afkar; Lisa Sabitillah; Juniman Juniman; Nuriman Nuriman; Juliana Safitri; Rambang Muharramsyah; Nadia Aldyza (LPPM Universitas Almuslim, 2025)
This community service activity was conducted at UPTD SD Negeri 4 Bireuen, involving the principal, teachers, and fifth-grade students as partners. Interviews revealed that most students lacked interest in classroom learning and preferred games, while teachers were not yet proficient in implementing educational games in their instruction. To address this issue, the service team introduced web-based educational games, aiming to boost students' learning interest and motivation while providing an engaging learning medium. The activity methodology included material gathering, planning, coordination with the school, and the execution of an introductory session and simulation on December 16, 2024. The games introduced included Wordwall, Educandy, and Genially. The results demonstrated high enthusiasm among students and teachers for web-based educational games, which successfully enhanced student engagement and digital skills. It is concluded that web-based educational games serve as an effective, innovative solution for elementary school learning. Follow-up training for teachers and the development of games aligned with the curriculum are recommended to maximize the benefits.